PENERAPAN MODEL DIRECT LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PPKN SISWA SD NEGERI 23 KABUPATEN SORONG - Haryo Franky Souisa; Herlina Anita Kalapain (SOSCIED, 2023)
This study aims to improve student civics learning outcomes by applying the direct learning model in second-grade elementary students in Sorong Regency, Teluk Dore Village. We applied a pre-experimental design and used pretest-posttest by taking tests to students. This study benefit schools by increasing civics learning outcomes through direct learning model. The results of research regarding the application of the direct learning learning model can improve Civics learning outcomes, especially in living in harmony. Keywords : direct learning, civics, learning outcomes